DAVLAT MUASSASALARIDA ENERGIYA BOSHQARUV TIZIMINI YARATISHDA IOT VA SUN'IY INTELLEKTNI QO’LLASH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the importance and application of Internet of Things (IoT) and artificial intelligence (AI) technologies in energy management in government institutions. Energy consumption is an important issue for every country today, and innovative solutions are needed to save resources and solve environmental problems. With the help of IoT and artificial intelligence, the processes of monitoring, analyzing and controlling energy consumption are improved. This article examines the role of IoT and AI technologies in energy management, the advantages and disadvantages of their application in government institutions, and future prospects.
Keywords: : energy, IoT, artificial intelligence, management..